1994
DOI: 10.1038/sj.bdj.4808518
|View full text |Cite
|
Sign up to set email alerts
|

Validity of clinical judgements for the presence of secondary caries associated with defective amalgam restorations

Abstract: Eighty patients were selected, who were each deemed to require the replacement of a defective amalgam restoration. The patients had a mean age of 36.7 years and were dentally fit on average 40 months previously. The main reasons given for the replacement of the defective restorations were perceived radiographic secondary caries (31%), fracture of the restoration (20%), marginal defect (17%), and perceived secondary caries observed clinically (14%). Following the removal of the restorations, a highly significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
8
0
5
Order By: Relevance
“…Cross-sectional studies in the USA have reported similar results [Klausner and Charbeneau, 1985;Kelsey et al, 1981]. In Canada, the percentage of amalgam replacements because of secondary caries has been reported to be between 20 and 56% [Lavelle, 1976;Boyd and Richardson, 1985;MacInnis et al, 1991], whereas in Europe the percentages have been between 34 and 72 [Dahl and Eriksen, 1978;Mjör, 1981;Qvist et al, 1986Qvist et al, , 1990Allander et al, 1990;Jokstad and Mjör, 1991;Mjör and Toffenetti, 1992;Foster, 1994;Gruythuysen et al, 1996;Mjör and Qvist, 1997].…”
supporting
confidence: 51%
“…Cross-sectional studies in the USA have reported similar results [Klausner and Charbeneau, 1985;Kelsey et al, 1981]. In Canada, the percentage of amalgam replacements because of secondary caries has been reported to be between 20 and 56% [Lavelle, 1976;Boyd and Richardson, 1985;MacInnis et al, 1991], whereas in Europe the percentages have been between 34 and 72 [Dahl and Eriksen, 1978;Mjör, 1981;Qvist et al, 1986Qvist et al, , 1990Allander et al, 1990;Jokstad and Mjör, 1991;Mjör and Toffenetti, 1992;Foster, 1994;Gruythuysen et al, 1996;Mjör and Qvist, 1997].…”
supporting
confidence: 51%
“…Moreover, Hodges et al [1995] found an average difference of 187 m between gaps associated with secondary caries compared to a noncarious site. However, several investigations found that marginal defects were not necessarily associated with secondary caries incidence [Hamilton et al, 1983;Foster, 1994;Kidd et al, 1995Kidd et al, , 1996. However, considering the differences in study designs, one should not be surprised by these conflicting results.…”
Section: Discussionmentioning
confidence: 90%
“…Espelid and Tveit [1991] found for ra diographic caries diagnosis in the gingival area of class 11 restorations a sensitivity of 47% and a specificity of 88%, rising to 64 and 97%, respectively, when the radiographic examination was supplemented with 'clinical' findings. Foster [1994] concluded that the combined radiographic and clinical diagnosis of secondary caries as the reason for re placement of fillings was generally well founded (sensitiv ity 64%, specificity 79%). Fitzgerald et al [1994] found for radiographic diagnosis, after validation against the presence of bacteria, a sensitivity for secondary caries detection of 50% and a specificity for the absence of caries of 73%.…”
Section: Discussionmentioning
confidence: 99%